Peran Kapabilitas Pemasaran Digital dalam Meningkatkan Ketangkasan Proses Bisnis dan Kinerja Pemasaran - Wesly Tumbur ML Tobing; Lukman Santoso; Reni Veliyanti (Jurnal Riset dan Inovasi Manajemen, 2024)
The purpose of this research is to examine the role of business process agility in creating a significant relationship between digital marketing capabilities and marketing performance in construction companies in Java. The research method was carried out quantitatively by collecting data by distributing questionnaires through electronic forms and printed formats which were delivered directly to respondents where the respondent was a director working for a contractor company on the island of Java. The sampling technique was carried out purposively based on the criteria for a director who has worked for at least five years in a contractor company on the island of Java. Based on these criteria, there are 211 company directors who have met these criteria. Data were analyzed using statistical software AMOS 22. The results showed that digital marketing capabilities had a positive and significant effect on business process agility. Digital marketing capabilities have a positive and significant effect on marketing performance. Likewise, business process agility has a positive and significant effect on marketing performance